Perbandingan Hasil Belajar antara Siswa yang Menggunakan Media Digital dan Metode Ceramah di Kelas VIII E dan VIII F SMPN 1 Telagasari - Adinda Zahrah; Agnia Rahma Farhillah; Aulia Fitriani Ramadhan; Deliana Putri; Ahmad Aisy Zaki (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to compare student learning outcomes between digital media-based learning and conventional methods. The research subjects consisted of two classes: Class VIII E as the control class, which learned through lectures, dictation, and summarizing, and Class VIII F as the experimental class, which used PowerPoint, the Kahoot application, and instructional videos. The study was conducted over four meetings within four weeks. Pretests and posttests were used to measure learning improvement and analyzed using the n-gain formula. The results showed that the average n-gain score of the control class was higher than that of the experimental class. This indicates that although the experimental class used interactive digital media, the control class demonstrated better comprehension of the material, most likely due to the summarizing activity that helped students focus and internalize the content more deeply. These findings suggest that conventional methods involving active student engagement through note-taking and summarizing still have high effectiveness in learning, and the implications may serve as a consideration in designing instructional strategies suited to students' learning characteristics.